A Comparative Study on Different Methods of Inoculating Cowpea Using Microbial Fertilisers - Second, Ze Medjap Abel; Aoudou, Yaouba; Yvonne, Fuh Ngwa (Discoveries in Agriculture and Food Sciences, 2023)
This study was based on setting up a method of inoculating cow pea using microbial fertilizers. the study was designed to evaluate the effects of inoculating bio fertilizers made from rhizobium bacterial with cowpea seeds so as to propose strategies for sustainable management of it. After putting in place six experimental set up made up of mixtures of: cowpea and rhizobium alone, cowpea with rhizobium substrate, cowpea plus rhizobium and gray powder, cowpea with rhizobium and phosphor solubilizing microbes (PSM), with two control experiment of which one set up had no inoculants and the other had just gray powder. The following parameters were verified: the height of plants after two months, average number of nodules per treatment and identification of various diseases attack on the different treated seedlings. Primary data were subjected to analysis of variance (ANOVA). The following results were obtained: the set up made of cowpea with rhizobium and grey powder gave best results with 39.70 cm as average height, 48 as an average number of nodules on these treated plants, no diseases attack due to the fact that Rhizobium which is a bacterium is used alongside with another ingredient. Cowpea with rhizobium and PSM also gave interesting results with average nodules of 41; 36.11cm as average height of plants and no disease. Apart from cowpea treated just with rhizobium alone which also showed average results with 27cm as average height and 27 as average number of nodules with no disease incidence. The control experiments together with cowpea treated with no rhizobium showed negative results with various diseases attack such as angular leave spots disease on seeds treated with grey powder, damping off of seedling for seeds treated with rhizobium substrate, and yellow cercosporiose for seeds without treatment. As recommendation, it is advisable to inoculate cow pea seeds with other ingredients as grey powder before planting.